Sliding mode disturbance observer-based control of a twin rotor MIMO system. (July 2017) - Rashad, Ramy; El-Badawy, Ayman; Aboudonia, Ahmed
Abstract: This work proposes a robust tracking controller for a helicopter laboratory setup known as the twin rotor MIMO system (TRMS) using an integral sliding mode controller. To eliminate the discontinuity in the control signal, the controller is augmented by a sliding mode disturbance observer. The actuator dynamics is handled using a backstepping approach which is applicable due to the continuous chattering-free nature of the command signals generated using the disturbance observer based controller. To avoid the complexity of analytically differentiating the command signals, a first order sliding mode differentiator is used. Stability analysis of the closed loop system and the ultimate boundedness of the tracking error is proved using Lyapunov stability arguments. The proposed controller is validated by several simulation studies and is compared to other schemes in the literature. Experimental results using a hardware-in-the-loop system validate the robustness and effectiveness of the proposed controller. Abstract : Highlights: This paper develops an integral sliding mode controller for a MIMO system. The controller is augmented with a sliding mode disturbance observer. The proposed controller provides chattering-free continuous control signals. The actuator dynamics is handled by backstepping with a sliding mode differentiator. Simulation and experimental validation of the proposed control approach is carried out.